1977
DOI: 10.1104/pp.59.5.948
|View full text |Cite
|
Sign up to set email alerts
|

Blue light-induced Absorbance Changes in Membrane Fractions from Corn and Neurospora

Abstract: Blue light-induced absorbance changes were measured from differentially centrifuged membrane fractions from dark-grown coleoptiles of Zea mays L., and mycelia from an albino mutant of Neurospora crassa Actinic irradiation caused changes in absorbance consistent with a flavinmediated reduction of a b-type cytochrome. Both corn and Neurospora showed similar light-minus-dark difference spectra, dose response curves, and kinetics of dark recovery after irradiation. The photoreducible cytochrome system from Neurosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(50 citation statements)
references
References 6 publications
(11 reference statements)
3
47
0
Order By: Relevance
“…A blue light-induced absorbance change indicating reduction of a membrane bound b-Cyt (and with a possible connection to blue light physiology) has been proposed to be located in plasma membranes (6). It has also been shown that red light and methylene blue can be used as substitutes for blue light and endogenous photoreceptor, respectively (7).…”
mentioning
confidence: 99%
“…A blue light-induced absorbance change indicating reduction of a membrane bound b-Cyt (and with a possible connection to blue light physiology) has been proposed to be located in plasma membranes (6). It has also been shown that red light and methylene blue can be used as substitutes for blue light and endogenous photoreceptor, respectively (7).…”
mentioning
confidence: 99%
“…Although the presence of b-type cytochromes in higher plant PM was first reported by Brain et al (1977) and Jesaitis et al (1977), conclusive evidence was obtained only by Asard et al (1989) and Askerlund, Larsson & Widell (1989).The amount of b-type cytochromes in plant PM vesicles varies from 60 pmol mg -1 protein (Asard et al 1989) to 800 pmol mg -1 protein (Widell & Sommarin 1991). Spectra of reduced-minus-oxidized b-type cytochromes in plant PM show a typical absorption maximum between 555 and 563 nm (a-band of the spectra), depending on temperature and species .…”
Section: Hemesmentioning
confidence: 99%
“…When cytochromes were discovered to reside in the mitochondria, the theory of 'anion respiration' lost prominence (Robertson 1960(Robertson , 1991. The plant PM redox studies started again after two observations in the 1970s; it was shown that (i) iron acquisition of plants required an Fe 3+ reduction step (Chaney, Brown & Tiffin 1972), and (ii) a blue-light reducible b-type cytochrome was associated with membrane fractions from corn and Neurospora (Brain et al 1977). Marker enzyme studies demonstrated that the so-called light-inducible absorbance change (LIAC) activity cosedimented with the oligomycininsensitive Mg 2+ -ATPase and glucan synthase II activities, two proposed positive marker enzymes for the PM in higher plants Leong, Vierstra & Briggs 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The preferential quenching of the flavin triplet over the singlet excited state Flavins have been strongly implicated as the chromphore responsible for the myriad of blue light responses found in plants (10). Evidence concerning phototropism in corn (1,7,8) and Phycomyces (2, 5) and phototaxis in Euglena (3), in particular, have been interpreted to suggest that the flavin triplet state is the active species (2, 3). This conclusion is based mainly on the observations that potassium iodide, which effectively quenches flavin photoreactions in solution (9), inhibits the photoresponses of both corn and Euglena.…”
mentioning
confidence: 99%
“…Evidence concerning phototropism in corn (1,7,8) and Phycomyces (2,5) and phototaxis in Euglena (3), in particular, have been interpreted to suggest that the flavin triplet state is the active species (2,3). This conclusion is based mainly on the observations that potassium iodide, which effectively quenches flavin photoreactions in solution (9), inhibits the photoresponses of both corn and Euglena.…”
mentioning
confidence: 99%